Individualization of selection and training of female athletes in speed-power athletics from the perspective of gender identity - Eugeny Vrublevskiy; Anatoly Skrypko; Ryszard Asienkiewicz (Physical Education of Students, 2020)
Background and Study Aim. To develop and justify the criteria for morphogenetic markers of speed-power abilities of athletes and the main directions of individualization of the process of their preparation, taking into account the characteristics of the female body.